Adhesive-bonded timber-concrete composites – Experimental and numerical investigation of hygrothermal effects. (15th October 2016) - Eisenhut, Lars; Seim, Werner; Kühlborn, Sonja
Highlights: For timber-concrete composites the adhesive technology provides a rigid bond. The advantages of a dry construction method and of prefabrication are combined. The long-term behavior was investigated under practical environmental conditions. The influence of thermal-hygric effects and mechanical loading was investigated. Numerical calculation methods were developed to predict the long-term behavior. Abstract: The advantages of the two different building construction materials timber and concrete could be used effectively in timber-concrete composite constructions. The composite structure shows optimized load carrying capacity, better dynamic behavior, higher noise protection and higher thermally activatable mass in comparison to constructions that are entirely made from wood. So far, the bond between wood and concrete is usually provided by mechanical fasteners or formfitting connections. Mechanical fasteners lead to a more or less flexible connection. In the case of formfitting connections, the behavior depends on the geometry of the contact area. A "rigid bond" can be achieved by using adhesive technology and it is possible to combine the advantages of a "dry construction method" with those of prefabrication. The questions of the production technology and the short-term behavior of glued wood-concrete composite constructions were answered in previous research projects at the Department of Timber Structures and Building Rehabilitation at the University of Kassel. However, knowledge of long-term behavior for an application in construction practice was missing. This has been studied in detail in the last three years in the research project "BestKleb", funded by the German Federation of Industrial Research Associations AiF.